EFEKTIVITAS MEDIA VIDEO TUTORIAL DALAM MENINGKATKAN KEMAMPUAN MEMBUAT KREASI STOPLES BAGI SISWA TUNAGRAHITA RINGAN KELAS V (EKSPERIMEN DI SLB HIKMAH MIFTAHUL JANNAH PADANG) - Ria Velina (Universitas Negeri Padang, 2015)
Abstrak: This research was derived from the problems found at SLB Himah Miftahul Jannah Padang. Indicating that the use of conventional media made the students have less interest in vocational class learning process. They only showed their concern at the beginning of the class. This was an experimental research applied pre-experimental design and one group pretest-postest design. In this research, a pretest was given to the subject prior to the treatment (tutorial video), then it was followed by administering a posttest to them. The scores gotten from the pretest and postest were processed and compared by using U Mann Whitney test. Key: learning skill, mentally disable.